Intracompany reporting in the enterprise management system - Zadorozhnyi, Zenovii-Mykhailo; Ometsinska, Iryna (Herald of Economics, 2021)
Introduction. The modern conditions of enterprise operation have led to changes in management reporting approaches and have caused more discussions in nonfiction about its identity with intracompany reporting. Informatization of society, globalization processes in the economy and its sustainable development have led to the expansion of management reporting functions and to clear definition of main characteristics of intracompany reporting, which is created by the staff for its internal use with the adherence of principles of confidentiality. The impact of external factors, which are mostly negative nowadays (economic crisis, restrictions caused by the global pandemic, unfair actions of competitors, cyberattacks) require qualitative developments of intracompany reporting forms, which should ensure rapid detection of the negative changes at the enterprise and timely provide the information for its effective elimination.The purpose of the study lies in scientific and theoretical justification of the concept «intracompany reporting», in determination of the role for enterprise management and also in outlining the principles of reporting formation and techniques of its preparation taking into account the modern conditions of enterprises activity.Methods. In the research process the following methods were used: theoretical generalization, comparison, abstract-logical for distinguishing the concepts of «management reporting» and «intracompany reporting»; grouping, generalization,  analogy,  analysis and synthesis for identifying the principles of formation of intracompany reporting and its qualitative characteristics; modeling, induction and deduction, structural-logical, tabular for establishing the stages of reports formation at the enterprise and the techniques of its preparation.Results. The essence of management and intracompany reporting as an information field for necessary decisions making by their users is investigated. The role of intracompany reporting for enterprise management is established and it is proved that it is an integral part of management reporting. The formation and usage principles of intracompany reporting in the context of two groups are outlined: the principles that are used in the formation      of financial and intracompany reporting; principles that are used in the formation of intracompany reporting. The qualitative characteristics of such reporting are clarified. The stages of its formation at the enterprise are highlighted. The expediency of construction the intracompany reporting information map at the enterprise is established and its form  is offered. The necessity of development of Regulations (standard) of the intracompany reporting is proved. Perspectives. Further researches should be aimed at developing the Regulations (standard) of intracompany reporting, as well as formation of standardized forms of such reporting, taking into account enterprises’ branch peculiarities.